Looking at language - Keaney, Brian; Lucas, Bill. (Cambridge : New York : Cambridge University Press, 1994)
Looking at Language provides a core of Knowledge about Language, with examples and activities which serve a real purpose, developing pupils' sensitivity to the many different ways in which language can be used, and providing them with an appropriate vocabulary to describe its most important features.
Includes index.
Keywords: English language -- Usage -- Problems, exercises, etc; Language and languages; Communication